ESSENTIAL TEACHER’S FEEDBACK IN READING NARRATIVE TEXT - Ana Nur Hamidah; Afi Niamah (STKIP PGRI Jombang, 2019)
A crucial part of the learning process is feedback(Harmer, 2007:137). Teacher’s feedback is a teacher's response to the results of students workwhich isdone after the assessment or evaluation process. During the English learning process in eighth grade class of SMP Islam Mu’awanah Al-Hasyimiyah, especially in reading skills,the students have some problemsin reading comprehension. The main objective of the researchis to elaborate theimplementation of teacher’s feedback to improve the student’s reading skill in narrative text. The result of the test showed that there is an improvement of the student’s achievement in reading skill after the students got teacher’s feedback. In addition, based on the questioner and observation, the students' response to the teaching and learning process also supported the improvement.